Endoscopic submucosal dissection is safe and feasible, allowing for ongoing surveillance and organ preservation in patients with inflammatory bowel disease. (12th June 2021) - Lightner, Amy L.; Vaidya, Prashansha; Allende, Daniela; Gorgun, Emre
Abstract: Aim: Experience of endoscopic submucosal dissection (ESD) for colorectal lesions in the setting of inflammatory bowel disease (IBD) remains limited. The aim of this work was to determine the safety, feasibility and oncological outcomes of ESD in patients with IBD. Method: A retrospective review of all adult patients (≥18 years) with a known diagnosis of either ulcerative colitis (UC) or Crohn's disease (CD) who underwent advanced colonoscopy and ESD between 1 January 2014 and 1 October 2020. Data collected included patient demographics, disease characteristics, pathological variables and procedure‐related complication rates. Results: A total of 25 patients were included: 19 (76%) were male with a median age of 63 years and disease duration of more than 10 years. Sixteen had UC and nine had CD; the majority were taking corticosteroids, immunomodulators or monoclonal antibodies at the time of ESD. The median procedure time was 41 min and the majority ( n  = 18; 72%) utilized chromoendoscopy. The median lesion size was 30 mm: eight had low‐grade dysplasia, nine had high‐grade dysplasia and three had adenocarcinoma and underwent oncological resection. None had surgical intervention for complication of ESD or perforation. A total of 23 (88%) had a complete R0 resection. Over a median follow‐up of 19 months, three were found to have dysplasia excised in polyps and none had subsequent adenocarcinoma. Conclusion: ESD in the setting of IBD is safe and effective for complete removal of large neoplastic lesions, allowing for ongoing endoscopic surveillance and organ preservation rather than surgical intervention.